Role of the Sūfis During the Pandemic in a Society: COVID-19 in Nigeria as a Case Study - Abdur-Razzaq Mustapha Balogun Solagberu (Teosofia: Indonesian Journal of Islamic Mysticism, 2021)
COVID – 19 is the code given to an infectious disease called Coronavirus. It was on 31st December 2019 that World Health Organization (WHO) was kept informed of its discovery. It was speculated that the disease was first discovered in the Republic of China. It then spread from there to other countries of the world, including Nigeria. Multiple efforts were put in place in an attempt to halt its spread in the country, i.e., Nigeria. One of such was to lockdown the country. The pandemic and lockdown had various effects on society and its people in multiple ways. As a result, people found themselves in a state of frustration and anxiety, looking forward to a remedy and solution. This paper, therefore, determines to examine the role of the Sūfis during this kind of situation with the hope of bringing the role of the Sūfis into the limelight and to put it on record the Sūfi resilience and effort on the spiritual being of the Sūfi adherents at a particular time. The method adopted in this research is based on the interpretative approach in line with the disciplines of Islamic Studies, especially Sufism and history.  The main result of the study reveals that the pandemic has both positive and negative effects on people generally. Finally, through its teachings, Sufism provides resilience to the public, especially its adherents.